Blending Video-Reflexive Ethnography With Solution-Focused Approach: A Strengths-Based Approach to Practice Improvement in Health Care. Issue 1 (25th September 2019) - Mesman, J.; Walsh, K.; Kinsman, L.; Ford, K.; Bywaters, D.
Professionals seldom discuss those things that go well-rather the focus is often on problems, poor outcomes, and what does not go well. Exnovation is about illuminating the invisible or hidden strengths of existing practices in order to improve practice and is central to the contemporary, qualitative elicitation method: video-reflexive ethnography (VRE). VRE is a method to explore and articulate the taken for granted by means of short video clips of one's own work practice that provides a basis for sharing experiences, assumptions, questions, and concerns about the way things are done in order to effect practice improvement. Reflexivity is key to the method. The creation of a safe space for this shared reflexivity is essential. Improvement activities frequently draw upon problem-focused approaches that imply blame and fault. Such approaches can serve to close down discussion, give rise to anxiety, and inhibit the very improvements sought. In contrast, a strengths-based, solution-focused approach serves to create the safe place where shared practices, rather than individuals, are the center of attention. By focusing on what works well practitioners are encouraged to identify and build on existing strengths. A solution-focused approach used alongside VRE provides a scaffold for building improvement that is relevant to context. In this article, we discuss exnovation, the elicitation method of video-reflexivity, and the incorporation of a strengths-based solution-focused approach with VRE. We highlight the transformative and complementary qualities of these methods and draw upon practical examples from health care to demonstrate how they serve to strengthen and enhance each other.